The The Role of Ma'had Aly Sunan Drajat as a Pillar for Training Ulama Based on Turoats and Modern Academics - Nur Halim; Isna Finurika (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyse the role of Ma'had Aly Sunan Drajat in producing Islamic scholars based on the integration of classical texts and modern academic methodologies. The background of this study is based on the challenges of globalisation and the development of Islamic higher education, which demands the emergence of scholars who not only master classical texts (turats) but also have academic, methodological, and contextual competencies. This research uses a qualitative approach with a case study type. Data collection techniques were carried out through observation, in-depth interviews, and documentation, while data analysis used data reduction, data presentation, and conclusion drawing models. The results of this study indicate that Ma'had Aly Sunan Drajat plays a strategic role as a pillar in producing scholar cadres through a turats-based learning system combined with a modern academic approach, such as the use of research methodologies, scientific writing, and a structured evaluation system. This integration is realised in the curriculum, learning process, and academic and character development. With this model, graduates not only have a deep understanding of fiqh and classical Islamic scholarship, but are also able to respond to contemporary issues in an argumentative and systematic manner. This study confirms that the integration of turats and modern academics is a relevant educational model in strengthening the cadre of scholars in the modern era.